Pancreatic Cancer: What the Oncologist Can Offer for Palliation - Malcolm J Moore (Canadian Journal of Gastroenterology)
Because pancreatic cancer has a poor survival rate and only 20% of patients present with potentially resectable disease, a key goal of therapy is to provide palliation. The poor medical condition of many patients interferes with their ability to tolerate traditional chemotherapy. Recently, however, a nucleoside analogue, gemcitabine, has been developed. This drug is more effective than 5-fluorouracil (5-FU), can be used in patients who fail to respond to 5-FU and has only modest toxicity. Combination therapies including gemcitabine and other agents are being tested. Local radiotherapy seems to provide pain relief, but gastrointestinal toxicity is significant. The effect of combined modality therapy (5-FU with radiotherapy) on survival is unclear, and it does not prevent local disease progression. Some novel biological agents, including angiogenesis inhibitors, matrix metalloproteinase inhibitors, antisense compounds, inhibitors of cell signalling such as epidermal growth factor and vascular endothelial growth factor, and inhibitors of oncogene activation, are undergoing phase II and III trials in patients with pancreatic cancer. Among the most promising are farnesyl protein transferase inhibitors, which modulate K-ras function. Such an approach is promising for the treatment of pancreatic cancer because this tumour frequently exhibits mutation of the ras gene.